Narrative Studies in Western Criticism and Interdisciplinary A historical Studay [In Arabic] - Slioua, Hamida (Milev Journal of Research and Studies, 2022)
Researchers were assured that the bridges of dialogue between literature and the arts were connected, making cooperation between different areas of knowledge inevitable, and even necessary in modern critical studies. History has demonstrated the openness of narrative critics to neighboring fields. and this is confirmed for the integration of human knowledge, and proved that the tendency to L’interdisciplinary was found in the Western critical heritage early, and since the age of enlightenment. This article deals with the beginnings of L’interdisciplinary with the philosophers of art in the era of logic in the sixteenth century, and they had a leading role in activating the dialogue between literary critics, artists and philosophers in literary and cultural salons. The cognitive synergy between criticism and its neighboring fields of thought and culture is also evident in aesthetic works, especially with Lessing, Harris, Jean-Jacques Rousseau and Diderot, and the phenomenon is flourishing more from the eighteenth century with the Vogue of Aesthetic Studies, which prompted writers and intellectuals to taste the arts, the latter left its clear impact on Critical Studies in France and Europe in general, manifested in the tendency the likes of Gustav Lanson and Philippe Hamon, and the interplay with the critics of the new novel and counter-criticism has multiplied, and this is what the article continues by pleading steps of the historical method. He concludes with important findings on the beginnings of L’interdisciplinary in Western narrative studies and its development in response to doctrinal and historical changes, and the impact of intertextuality on the narrative and critical literary aspect.